2007
DOI: 10.3390/12071341
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 4-Aryl Substituted 3,4-Dihydropyrimidinones Using Silica-chloride Under Solvent Free Conditions

Abstract: This paper describes an improved procedure for the efficient and facile synthesis of 4-aryl substituted 3, 4-dihydropyrimidinones under mild reaction conditions with excellent yields using inexpensive silica chloride under solvent free conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(42 citation statements)
references
References 16 publications
0
40
0
Order By: Relevance
“…The catalyst silica chloride was prepared as per a reported method, [6] and acetic anhydride was prepared from sodium acetate and acetyl chloride. Yields refer to yield of isolated products.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The catalyst silica chloride was prepared as per a reported method, [6] and acetic anhydride was prepared from sodium acetate and acetyl chloride. Yields refer to yield of isolated products.…”
Section: Methodsmentioning
confidence: 99%
“…[5] The wide application of solid-supported reagents and catalysts is due to ease and safety in handling, rate enhancement, good yields, easy workup procedures, and economy. An inexpensive silica chloride can be prepared easily by treating thionyl chloride with silica gel [6] and is a better reagent when compared to thionyl chloride or trimethyl silyl chloride (Scheme 1). Once the reaction gets completed, the catalyst can be filtered, washed with chloroform, and reused without decrease in activity for three runs.…”
Section: Introductionmentioning
confidence: 99%
“…The literature survey has revealed that there is relatively little number of reports on the use of true heterogeneous catalyst for Biginelli reaction. Most of the methods are based upon the impregnation of toxic substances such as Cl 2 , H 2 SO 4 , and NaHSO 4 on Silica gel [32][33][34]. A truly heterogeneous catalyst such as montmorillonite KSF have been previously demonstrated for this reaction, but the reaction time (10-48 h) is relatively longer [35,36].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, new methods for the synthesis of dihydropyrimidinones have been developed by different groups [6][7][8][9][10][11][12][13][14][15]. It is still highly valuable to develop newly direct approaches for the efficient synthesis of DHPMs due to the continued importance of these compounds core in organic and medicinal chemistry.…”
Section: Introductionmentioning
confidence: 99%